Simple Preparation of β-Amino Alcohols Possessing a tert-Butyl Group at the α-Carbon - Zacharia, James T.; Tanaka, Takanori; Uesaka, Yumiko; Hayashi, Masahiko (Synthesis, 2012)
Simple preparation of β-amino alcohols possessing a tert-butyl group at the α-carbon was achieved. These β-amino alcohols proved to work effectively as catalysts in the enantioselective alkylation of aldehydes.
Keywords: amino alcohols; alkylation; organocatalysis; enantioselectivity; rearrangements